REVITALISASI KOLAM LILA ARSANA SEBAGAI ALTERNATIF WISATA OLAHRAGA AIR DI KLUNGKUNG - Putra, I Wayan Yogik Adnyana; Wicaksana, Gde Bagus Andhika (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
Historical relics bring great benefits in the field of historical and cultural tourism. Semarapura city of Klungkung regency has almost 330 historical sites, such as: Puri, Pura, Ancient Building, Heritage, Kertagosa Park and Lila Arsana Pool. Today the number of historic buildings that are still surviving is decreasing, along with the lack of government control and also the occurrence of natural disasters. Therefore, the seriousness and awareness of all stakeholders, whether it is the government and the tourism industry, including the local community to develop and tourism tourism Pool Lila Arsana which is a pool of Puri Klungkung heritage built since 1930. Therefore it is necessary to study in revitalizing the area. This paper describes among others: Scenario of regional arrangement; Masterplan of regional arrangement; development and investment programs; Direction of program implementation control; as well as the proposed physical activity package, so that the revitalization area will be more integrated with the city system. In addition, good cooperation between all elements of the community is needed to maintain and preserve and develop the existing potentials. If that is realized Pool Lila Arsana will make a big contribution for Semarapura City government through, economic improvement for local people and also can be an alternative of water sports which have culture, religion and history.